Assessment of the influence of phytocomposition on the sensory characteristics of bakery products - O. V. Pavlova; A. S. Kucher; V. N. Orobinskaya (Современная наука и инновации, 2025)
One of the current trends in the production of fortified food products is the replacement of wheat flour with other types of raw materials in the recipe for bakery products. A study was conducted to study the effect of a phytocomposition based on dogwood fruits and secondary raw materials of apples and pumpkin on the organoleptic quality indicators of bread samples. In the recipe, part of the wheat flour was replaced with a phytocomposition in the amount of 5-20 %. The amount of other ingredients in the recipe remained unchanged. A comparative assessment of the sensory quality indicators in fortified and control samples is shown. The use of a plant additive obtained by drying and grinding technology as a non-traditional component of bakery products allows you to get a product with acceptable organoleptic properties. Studies of the effect of replacing wheat flour on the organoleptic indicators of fortified bread allow us to conclude that the additive has a pronounced effect on the appearance, color and condition of the crumb. The best sample was the one with flour replaced with a plant composition in the amount of 10 %.